2012
DOI: 10.2197/ipsjjip.20.435
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bound of Face Guards of Polyhedral Terrains

Abstract: Abstract:We study the problem of determining the minimum number of face guards which cover the surface of a polyhedral terrain. We show that (2n − 5)/7 face guards are sometimes necessary to guard the surface of an n-vertex triangulated polyhedral terrain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Notice that a polyhedral terrain has a different structure than a city with vertical buildings. The results related to guarding polyhedral terrain focus on edge and face guards [20,13,5,10,26,25].…”
Section: Polyhedral Terrain Resultsmentioning
confidence: 99%
“…Notice that a polyhedral terrain has a different structure than a city with vertical buildings. The results related to guarding polyhedral terrain focus on edge and face guards [20,13,5,10,26,25].…”
Section: Polyhedral Terrain Resultsmentioning
confidence: 99%
“…A terrain whose bounded faces are triangles is called a triangulated terrain. These special terrains are studied in [9,10,11], where it is shown that computing the minimum number of closed face guards in a given triangulated terrain is NP-hard. Here we strengthen this result by showing that such a minimum is even NP-hard to approximate within a logarithmic factor, for both open and closed face guards, provided that terrains are not necessarily triangulated.…”
Section: Minimizing Face Guards 41 Hardness Of Approximationmentioning
confidence: 99%
“…It is known that ⌊(2n − 5)/7⌋ is the lower bound and ⌊n/3⌋ is the upper bound for the number of face guards of an n-vertex triangulated polyhedral terrain [10]. After that, both the lower and upper bounds are shown to be ⌊(n − 1)/3⌋ [11].…”
Section: Introductionmentioning
confidence: 99%